(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article focuses on the need to base the development of students’ talent on certain psychological laws in the teaching of concrete and natural sciences, and on the individual-psychological characteristics of a gifted person manifested in intellectual-theoretical activity.